2022
DOI: 10.1101/gr.276251.121
|View full text |Cite
|
Sign up to set email alerts
|

Snake venom gene expression is coordinated by novel regulatory architecture and the integration of multiple co-opted vertebrate pathways

Abstract: Understanding how regulatory mechanisms evolve is critical for understanding the processes that give rise to novel phenotypes. Snake venom systems represent a valuable and tractable model for testing hypotheses related to the evolution of novel regulatory networks, yet the regulatory mechanisms underlying venom production remain poorly understood. Here, we use functional genomics approaches to investigate venom regulatory architecture in the prairie rattlesnake and identify cis-regulatory sequences (enhancers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…The snake has been on the medical emblem for over two millennia, based on the Greek God of healing and medicine Asclepius, who held a staff with a snake coiled around it (Antoniou et al 2011). The advance of science has overtaken centuries of superstition about snakes, and snake venom research now spans the medical, pharmacological, ecological and molecular evolutionary domains (Chiappinelli 1983;Dutertre and Lewis 2010;Giorgianni et al 2020;Oliveira et al 2022a;Perry et al 2022;Saviola et al 2014;Whittington et al 2018), with an exponential increase in publications over the last century (Sofyantoro et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The snake has been on the medical emblem for over two millennia, based on the Greek God of healing and medicine Asclepius, who held a staff with a snake coiled around it (Antoniou et al 2011). The advance of science has overtaken centuries of superstition about snakes, and snake venom research now spans the medical, pharmacological, ecological and molecular evolutionary domains (Chiappinelli 1983;Dutertre and Lewis 2010;Giorgianni et al 2020;Oliveira et al 2022a;Perry et al 2022;Saviola et al 2014;Whittington et al 2018), with an exponential increase in publications over the last century (Sofyantoro et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…More recently the evolutionary biology of toxins and venom has been investigated, including both inter-and intraspecific venom variation and its evolutionary and ecological significance (Margres et al 2021;Mora-Obando et al 2020;Rautsaw et al 2019;Zancolli et al 2019). Venom is also being used as a model for understanding gene duplication, expression and regulation, and molecular evolution (Giorgianni et al 2020;Hargreaves et al 2014;Perry et al 2022;Whittington et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NFI family binding sites are highly correlated with the center of nucleosome depletion regions, suggesting that their binding directly shapes local chromatin structures and can function as pioneer factors (Grossman et al 2018; Adam et al 2020). Pioneer factors are the first factors to engage target sites in chromatin and recruit histone modifying proteins, similar to many other identified viperid toxin gene TFs such as AP-1, CREB3, and FOX family TFs (Zaret and Carroll 2011; Perry et al 2022). In addition, we found multiple CREs and associated trans- factors that were upregulated in viperids unique to group II PLA 2 s (RAR, USF1, and T3R), as well as varying upregulation of these factors between the two rattlesnake species, highlighting potential regulatory differences that could contribution to venom variation between and within the two snake families.…”
Section: Discussionmentioning
confidence: 91%
“…These studies have identified cis -regulatory elements (CRE) that regulate the expression of genes encoding 3FTx and group I PLA 2 expression in the Javan Spitting Cobra ( Naja sputatrix ) (Jeyaseelan et al 2000; Ma et al 2001; Ma et al 2002), the pseutarin C catalytic subunit in the Eastern Brown Snake ( Pseudonaja textilis ) (Kwong et al 2009), and silencer AG-rich motifs in the first intron of the pseutarin C catalytic subunit gene (Han et al 2016). Investigations of viperids have found α1− and β−adrenoceptor signaling as a mechanism activating transcription factors (TFs) NF-kB and AP-1 to initiate toxin synthesis in the Jararaca ( Bothrops jararaca ) (Yamanouye et al 1997; Luna et al 2009), tissue-specific TF ESE-3 upregulated group II PLA 2 s genes in the Habu ( Protobothrops flavoviridis ) (Nakamura et al 2014), and CREs for binding GRHL-and NFI-family TFs were enriched within SVMP, SVSP, and group II PLA 2 gene promoters in the Prairie and Tiger rattlesnakes ( Crotalus viridis and C. tigris , respectively) (Schield et al 2019; Margres et al 2021; Perry et al 2022), in addition to co-opted TFs from the Unfolded Protein Response (UPR) pathway (Perry et al 2022). Current evidence suggests that for the viperids C. viridis and C. tigris, toxin gene expression is regulated by chromatin structure, TFs, and gene methylation levels (Schield et al 2019; Margres et al 2021).…”
Section: Introductionmentioning
confidence: 99%